Antibiotikaresistens hos bakterier isolerade från friska hundar i Sverige : indikatorbakterier E. coli & Enterococcus spp samt Staphylococcus spp isolerade från hud - Zwenson, Johanna (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2007)
Objective: To determine the frequency of antimicrobial resistance in bacteria from healthy Swedish dogs and whether they are carriers of methicillinresistant Staphylococcus aureus (MRSA).